PEMETAAN POTENSI PENGEMBANGAN TERNAK KERBAU DI SELATAN - Anshar, Muhammad (Teknosains, 2013)
This study aimed to analyze the potential development of buffaloes in South Sulawesi with quntitatif method approach. Primary and secondary data were used in analyzing. The analysis showed that South Sulawesi have a large potenies for the development of buffaloes. In social perspective, the buffalo has been maintained by generations. Particularly in Toraja regency, buffalo is an important part in traditional ceremonies. Spotted buffalo habitat (tedong bonga) comes from this district, with high economic value of livestock commodities. Moreover, the potential labor forces is very supportive in the development of buffaloes, in terms of manpower, knowledge and farmer skills, and support in increasing the number and capacity of extension officers. Other districts also have potential to developing the ruminants such as buffaloes are Luwu Timur and Selayar District, where the utilization of its capacities seen from the availability of forage fodder, only used respectively by 5.35% and 10.23%. Beside it, on the buffalo development base area, Tana Toraja still have a chance to increase the population up to 25.563,77 AU; 16.440,05 AU in Toraja Utara Regency and surrounding districts such as Luwu, Luwu Utara, Luwu Timur and Enrekang.Key words: development potencises, buffalo